Gender Differences in Digital Learning During COVID-19: Competence Beliefs, Intrinsic Value, Learning Engagement, and Perceived Teacher Support - Korlat, Selma; Kollmayer, Marlene; Holzer, Julia; Lüftenegger, Marko; Pelikan, Elisabeth Rosa; Schober, Barbara; Spiel, Christiane (Frontiers in Psychology, 2021)
The spread of the COVID-19 pandemic quickly necessitated digital learning, which bore challenges for all pupils but especially for groups disadvantaged in a virtual classroom. As some studies indicate persistent differences between boys and girls in use of technologies and related skills, the aim of this study was to investigate gender differences in the digital learning environment students faced in spring 2020. Previous studies investigating gender differences in digital learning largely used biological sex as the only indicator of gender. This study includes both biological sex and gender role self-concept in order to investigate the role of gender in different components of this stereotyped domain in a more differentiated way. A total of 19,190 Austrian secondary school students (61.9% girls, Mage = 14.55, SDage= 2.49, age range 10-21) participated in an online study in April 2020 and answered questions regarding their competence beliefs, intrinsic value, learning engagement and perceived teacher support during the pandemic-induced school closures. Results showed higher perceived teacher support, intrinsic value and learning engagement among girls than boys, while no significant sex differences were found in competence beliefs regarding digital learning. Furthermore, our results indicated clear benefits of an androgynous gender role self-concept for all studied components of digital learning. Implications of the findings for theory and practice are discussed.